Interpersonal Counseling (IPC) for Depression in Primary Care - WEISSMAN, MYRNA M. (Am J Psychother, 2014)
Interpersonal Counseling (IPC) comes directly from interpersonal psychotherapy (IPT), an evidenced-based psychotherapy developed by Klerman and Weissman. It [IPC?] is a briefer, more structured version for use primarily in non-mental health settings, such as primary care clinics when treating patients with symptoms of depression. National health-care reform, which will bring previously uninsured persons into care and provide mechanisms to support mental health training of primary care providers, will increase interest in briefer psychotherapy. This paper describes the rationale, development, evidence for efficacy, and basic structure of IPC and also presents an illustrated clinical vignette. The evidence suggests that IPC is efficacious in reducing symptoms of depression; that it can be used by mental health personnel of different levels of training, and that the number of sessions is flexible depending on the context and resources. More clinical trials are needed, especially ones comparing IPC to other types of care used in the delivery of mental health services in primary care.